How market orientation impacts customer's brand loyalty and buying decisions - Elizabeth Serra; Mariana de Magalh\~aes; Rui Silva; Galv\~ao Meirinhos (Journal of Risk and Financial Management, 2022)
As retail management has become increasingly demanding, it is imperative that retailers use market orientation to promote and increase loyalty to their private labels. This can be important in efforts to differentiate themselves from their competition. The focus of this study is to understand how these factors impact the loyalty of customer purchase decisions, through the link between the potential for brand risk and brand commitment, in order to facilitate customer orientation and brand loyalty. An online survey was conducted with a sample of 2900 consumers in Portugal and Spain. This study analyzed two distinct and high involvement product categories: Denomination of Origin (DOC) wine and anti-wrinkle cream. Structural equation modeling methodology was used to analyze the relationship between different constructs. It was found that there is no direct correlation between customer orientation and brand loyalty. However, this connection is critical when the two mediating variables of brand risk and brand commitment are accounted for. Another important finding relates to the values and differences identified between the two product categories. The results obtained show the importance of risk and commitment for high involvement products. In practice, this justifies brands explicitly managing these factors, because they can translate into loyalty behaviors. The results also contribute to demystifying the market for more complex products, particularly when the choice and risk process is more complex.
Keywords: 650; brand commitment; brand loyalty; brand risk; customer orientation; private label; product social value